3D-printable zwitterionic nano-composite hydrogel system for biomedical applications. (October 2020) - Sällström, Nathalie; Capel, Andrew; Lewis, Mark P; Engstrøm, Daniel S; Martin, Simon
Herein, the cytotoxicity of a novel zwitterionic sulfobetaine hydrogel system with a nano-clay crosslinker has been investigated. We demonstrate that careful selection of the composition of the system (monomer to Laponite content) allows the material to be formed into controlled shapes using an extrusion based additive manufacturing technique with the ability to tune the mechanical properties of the product. Moreover, the printed structures can support their own weight without requiring curing during printing which enables the use of a printing-then-curing approach. Cell culture experiments were conducted to evaluate the neural cytotoxicity of the developed hydrogel system. Cytotoxicity evaluations were conducted on three different conditions; a control condition, an indirect condition (where the culture medium used had been in contact with the hydrogel to investigate leaching) and a direct condition (cells growing directly on the hydrogel). The result showed no significant difference in cell viability between the different conditions and cells were also found to be growing on the hydrogel surface with extended neurites present.